Ayiat of Justices at Judgment of Swrat Al Nisah - Omar Abd Al khafoor Mohammed, (Islamic Sciences Journal, 2026)
The researcher seeks to uncover the implications and rulings of justice through a study of Surah An-Nisa (Chapter 4 of the Quran), as well as to deduce the Quranic methodology in its approach to social justice and the establishment of the principle of equality among individuals. The importance of this research lies in demonstrating the value of justice in Islamic law, particularly as presented in the Holy Quran. The study reveals that justice in Surah An-Nisa is a binding value with a prescriptive character, beginning with refining one's relationship with oneself and then extending to one's relationships with others and society, regardless of status, kinship, or personal interests. It also emphasizes the connection between the command to be just and trustworthy and the oversight of God, the All-Hearing, the All-Seeing, thus reinforcing the faith-based dimension of adherence to Islamic law and ensuring its continuity in private and public life.of the study.